Heterobimetallic Pd(0) complexes with Pd→Ln (Ln = Sc, Y, Yb, Lu) dative bonds: rare-earth metal-dominated frustrated Lewis pair-like reactivity. Issue 35 (25th August 2020) - Du, Jun; Zhang, Yanan; Huang, Zeming; Zhou, Shuangliu; Fang, Huayi; Cui, Peng
Abstract : A series of Pd–Ln complexes with Pd→Ln (Ln = Sc, Y, Yb, Lu) dative bonds exhibited notable dynamic structural features and unexpected frustrated Lewis pair-like reactivity. Abstract : A series of heterobimetallic Pd–Ln complexes with Pd→Ln (Ln = Sc, Y, Yb, Lu) dative bonds were synthesized via sequential reactions of phosphinoamine Ph2 PNHAd with (Me3 SiCH2 )3 Ln(THF)2 and (Ph3 P)4 Pd or (COD)Pd(CH2 SiMe3 )2 . These complexes were characterized by NMR spectroscopy, X-ray diffractions, and computational as well as electrochemical studies, which revealed Pd→Ln dative interactions that vary according to the ionic radii of Ln 3+ . Furthermore, the notable dynamic structural features of the Pd–Ln complexes in solution and their unexpected frustrated Lewis pair-like reactivity toward aryl halides and ketene were also studied.